Pengaruh Emotional Intelligence Terhadap Organizational Citizenship Behavior (OCB) Pada Perawat Di Kota Makassar - Selna Wahyuningsih; Ahmad; St. Hadjar Nurul Istiqamah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The purpose of this study was to see the influence of emotional intelligence on Organizational Citizenship Behavior (OCB) in nurses. Respondents used in this study were nurses in Makassar City, totaling 180 people. This research uses quantitative methods. The data collection method was carried out using an adapted emotional intelligence scale and organizational citizenship behavior (OCB) scale. The analytical method used in this research is a spearman rho test. The results of this study indicate that there is a positive influence of emotional intelligence on organizational citizenship behavior (OCB) of 64,1% in nurses in Makassar City.